Adjustment Tendencies Among Transiting Students: A Mediation Analysis Using Psychological Wellbeing Indices - Ofem, Usani (International Journal of Education and Cognitive Sciences, 2022)
Most students have difficulties in getting use to the new environment that they find themselves especially when the settings of their previous school is different from where they are admitted newly. The study sought to carry out a mediation analysis of the link between psychological wellbeing and adjustment of transiting students. The study adopted a quantitative approach with a total of 1560 students used for the study. The instrument used for the study was a question that was validated appropriately. Data collected were analysed using the partial least squares structural equation modelling (PLS-SEM) to examine the direct and indirect effect of the psychological wellbeing on adjustment tendencies as well and variance explained by the variables. The results showed that there exist a direct effect of environmental mastery and self-acceptance on academic, emotional, and social adjustment. Personal relations have a direct effect on emotional adjustment and social adjustment but not for academic adjustment. Self-acceptance has a negative direct effect on environmental mastery. A significant direct effect exists between environmental mastery and positive relations (PR), self-acceptance has a direct effect on environmental mastery and self-acceptance (SEA) on positive relations. A partial mediation effect exists between self-acceptance and academic adjustment as mediated by environmental mastery but not with self-acceptance and academic adjustment as mediated by positive relations among others. Psychological wellbeing when combined, contribute to the variances in adjustment tendencies. Conclusions and further implication of the findings were discussed.